2001
DOI: 10.1159/000050843
|View full text |Cite
|
Sign up to set email alerts
|

Central Retinal Vein Occlusion and Nonarteritic Ischemic Optic Neuropathy in 2 Patients with Mild Iron Deficiency Anemia

Abstract: We report on 2 patients with ophthalmologic complications associated with mild iron deficiency anemia. Case 1, a 37-year-old female patient, presented after 4 days of blurred vision in her left eye. Ophthalmoscopic and angiographic findings were consistent with the diagnosis of central retinal vein occlusion (CRVO). Further hematologic investigation into possible causes disclosed mild iron deficiency anemia (Hb 9.4 g/dl, hematocrit 30.5%). After the patient’s visual acuity had worsened progressively to 20/50, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 7 publications
(11 reference statements)
1
15
0
2
Order By: Relevance
“…17,18 In previous studies, retinal vein occlusion, ischemic retinopathy, and ischemic optic neuropathy have been reported in patients with IDA. 6,19 In addition, Turkyilmaz et al 20 reported that the average retinal nerve fiber layer and the retinal nerve fiber layers of the superior and inferior quadrants were significantly thinner in the IDA group than in the control group. Furthermore, Carraro et al 7 suggested that severe anemia plays a significant role in the pathogenesis of retinal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 In previous studies, retinal vein occlusion, ischemic retinopathy, and ischemic optic neuropathy have been reported in patients with IDA. 6,19 In addition, Turkyilmaz et al 20 reported that the average retinal nerve fiber layer and the retinal nerve fiber layers of the superior and inferior quadrants were significantly thinner in the IDA group than in the control group. Furthermore, Carraro et al 7 suggested that severe anemia plays a significant role in the pathogenesis of retinal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…This disturbance causes retinopathy, including retinal vein and retinal artery occlusion. 6,21 The mechanism of the disturbance of the retinochoroidal circulation in patients with IDA remains unclear; however, iron deficiency may contribute to a hypercoagulable state by affecting blood flow patterns within the vessels because of reduced deformability and increased viscosity of microcytic red blood cells. 22 The other postulated mechanism behind hypercoagulability was reduced antioxidant defense due to IDA and reduced activity of glutathione peroxidase, which corresponds to increased platelet aggregation, reactive thrombocytosis, and elevated factor VIII levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disturbance causes various ophthalmic disorders, including retinal vein occlusion and retinal artery occlusion (6)(7)(8)(9). It has been speculated that the disturbance of retinochoroidal circulation is caused by formation of thrombosis due to hypoxia-induced injury of angioendothelial cells, deregulation of the coagulation/fibrinolytic system and thrombocytosis in iron deficiency anemia (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there have been a few reports on an association with hematologic disorders [1,11], including anemia. Patients with this condition have a substantially elevated risk of intraretinal hemorrhages or retinal vein occlusion [4]. However, in light of the fact that our patient's hemoglobin level was only mildly decreased (11.9 g/dl), and platelet count or hematocrit levels were normal, it seems less likely that these factors may have conributed to the development of her subhyaloidal hemorrhage.…”
Section: Commentmentioning
confidence: 55%